Methylotrophic yeast Candida boidinii enhances the colonization of plant growth-promoting yeast Papiliotrema laurentii in the phyllosphere - Shigeta, Kana; Shiraishi, Kosuke; Schroll, Moritz; Lauer, Rebekka; Keppler, Frank; Sakai, Yasuyoshi; Yurimoto, Hiroya (Frontiers in microbiology, 2025)
Methanol-utilizing microbes are ubiquitous in the phyllosphere, where they assimilate methanol released from pectin, the major component of the plant cell wall. While methylotrophic bacteria Methylobacterium spp. are well studied for their symbiotic relationships with the host plants, the ecology and functional roles of methylotrophic yeasts on plants remain poorly understood. In the effort to isolate yeasts from 26 phyllosphere samples, we identified Candida boidinii as the only methylotrophic yeast, while the remaining isolates, categorized into 17 species in 12 genera, lacked this metabolic trait. To obtain insight into the role of methylotrophic yeasts in the phyllosphere, we investigated the interaction of C. boidinii with a plant growth-promoting yeast (PGPY), Papiliotrema laurentii, one of the identified yeast species during isolation. We found that the colonization of P. laurentii was enhanced by the presence of C. boidinii on Arabidopsis thaliana leaves. Co-cultivation assays revealed that the cell yield of P. laurentii was enhanced by C. boidinii during cultivation on pectin and that the methanol-utilizing ability and pectin methylesterase (PME) activity of C. boidinii contributed to this enhancement. Stable carbon isotope labeling of pectin methylester groups unambiguously confirmed their assimilation by C. boidinii, but not by P. laurentii. These findings suggest that C. boidinii not only survives in the phyllosphere by utilizing pectin-derived methanol but also contributes to the fitness of other yeast species through metabolic cooperation. This study provides new insights into the niche construction and survival strategies of phyllosphere methylotrophic yeasts, highlighting their potential role in shaping microbial community dynamics and promoting beneficial plant-microbe interactions.